Building a comics collection in the University of the Philippines Library a feasibility study - Cruz, Alvin Zernan R.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
Comic books have been existed in the nimbus of pop culture since their conception. It is said that our national hero Dr. Jose Rizal drew the first cartoom strip tht saw publication here in the Philippines (Roxas, 1985). But the formal history of the Philippine komiks started in 1926 when Antonio S. Velasquez saw the potentials and possibilities of this medium.
This study aims to evaluate the komiks collection of th Filipiniana Serials Section of the UP Main Library based on the four components of the feasibility study, Namely: user needs analysis; technical feasibility; financial feasibility; and organizational and management feasibility.
The study used the evaluative type of research. The komiks collection of the Filipiniana Serial Section as the unit of analysis was evaluated using the four components of the feasibility study. For the user needs analysis, sampling of respondents use the method of convenience sampling. There are two hundred ten (210) respondents comprised the population of the study. For the three feasibility components, the head librarian of the Filipiniana Serial Section and the three professors (one for every college) from CAL, CFA, and CHE who are teaching subjects related to comics were interviewed.
Based on the result of the survey, majority of them have a great regard on the establishment of a separate comic books Section in the UP Main Library. In this result, we can surmise that in this feasibility, it meets the standard requirement for the user needs analysis. On the other hand, the Komiks collection failed to meet the standard requirements of financial, technical, and organizational/management feasibility aspects. Results were not new since the said collection has no separate section. The library does not allocate budget for the Komiks Collection. A professional librarian manages it, but her focus was on the other collections contained in the Filipiniana Serial Section.
The researcher recommends the following: (1) In establishing a Comic Books Section, it must have a separate place firm the other sections in the UP Main Library; (2) It must be provided with adequate and continuing budgetary support from the University; (3) The library section to be establish can improve on its collection by asking donations from the different comic books dealers, UP alumni who have personal collections of comic books, and other private individuals and institutions who wanted to help; (4) The need to have a database is imperative; (5) Collection must be cataloged, indexed and classified following the UP Main Library classification system or a more simplified scheme; (6) The need to have the library equipments and facilities needed in establishing the library section is necessary; and (7) These criteria in selecting comic books must be followed: a) literary, artistic and technical values; b) reputation and qualifications of the creator, publisher of producer, ; c) educational values of the comic books; d) it support the curriculum; and e) its updateness.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- Libraries; Collection development (libraries) -- Comic books, strips, etc. -- Philippines -- Quezon City; Comic books, strips, etc. -- Philippines -- Quezon City